2020
DOI: 10.22201/ia.01851101p.2020.56.02.09
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics Around an Asteroid Modeled as a Mass Tripole

Abstract: The orbital dynamics of a spacecraft orbiting around irregular small celestial bodies is a challenging problem. Diffculties to model the gravity field of these bodies arise from the poor knowledge of the exact shape as observed from the Earth. In order to understand the complex dynamical environment in the vicinity of irregular asteroids, several studies have been conducted using simplified models. In this work, we investigate the qualitative dynamics in the vicinity of an asteroid with an arched shape using a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 34 publications
(62 reference statements)
0
1
0
Order By: Relevance
“…Lan et al (2017) showed that, from five parameters (which are determined with the help of the polyhedral model), it is possible to define the geometric shape and to obtain the physical characteristics of a real asteroid and to obtain its gravitational field. In order to generalize the work of Lan et al (2017), Barbosa Torres dos Santos et al (2020 investigate the qualitative dynamics in the vicinity of an asteroid with an convex shape using a rotating tripole model from a semi-analytical study.…”
Section: Introductionmentioning
confidence: 99%
“…Lan et al (2017) showed that, from five parameters (which are determined with the help of the polyhedral model), it is possible to define the geometric shape and to obtain the physical characteristics of a real asteroid and to obtain its gravitational field. In order to generalize the work of Lan et al (2017), Barbosa Torres dos Santos et al (2020 investigate the qualitative dynamics in the vicinity of an asteroid with an convex shape using a rotating tripole model from a semi-analytical study.…”
Section: Introductionmentioning
confidence: 99%